Elastic-plastic analysis of metallic shells at finite strains - Campello,Eduardo Moraes Barreto (2007)
The geometrically-exact finite-strain variable-thickness shell model of [1] is reviewed in this paper and extended to the case of metallic elastoplastic shells. Isotropic elasticity and von Mises yield criterion with isotropic hardening are considered. The model is implemented within a triangular finite element and is briefly assessed by means of two numerical examples.